Understanding the Values of Pancasila and the Kebhinekaan Tunggal Ika Diversity in the Middle of the Diversity of Students - Riyanti, Rahayu Febri; Rahmawati, Fitri Puji; Widyastuti, Arifah Dwi; Hasna, Lina (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
In the midst of current technological advancements, students lack a comprehensive understanding of the actual impact of internalizing the values of unity in diversity (Bhinneka Tunggal Ika) and Pancasila on the formation of the national identity of learners. Furthermore, there is a gap in knowledge regarding how this process can positively contribute to the development of inclusive, tolerant, and harmonious attitudes within the educational environment.The internalization of Pancasila values in schools is considered a crucial step towards strengthening the national identity of Indonesia, involving elements of diversity, Pancasila, and religiosity. This study employs a qualitative descriptive approach, utilizing observation and interviews. The subjects of this research are class teachers, subject teachers, and the vice principal in charge of the curriculum. The data validity technique used is triangulation method with an interactive data analysis model developed by Miles and Huberman.The findings indicate that Pancasila values provide a solid foundation for embracing diversity in the school environment. By internalizing Pancasila values, schools can enhance understanding and appreciation for the diverse cultural, religious, ethnic, and other elements present in the school ecosystem.